ANALISIS KAPASITAS PUNTIR ELEMEN BALOK BETON MUTU TINGGI DENGAN SUBSTITUSI ADITIF, AGREGAT HALUS SERTA AGREGAT KASAR (PENGGUNAAN FLY ASH BATU BARA, PASIR POZZOLAN DAN CANGKANG SAWIT) - Geminingsih Nastitip; Teuku Budi Aulia; Muttaqin Muttaqin (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Along with the construction development which is not symmetrical and both the column and the beam made small then the torsion load highly affect the building structure. The torsion load often occurs in the building components such as beam, column and the joint of column and beam. The loads of floor plates and small beam will create a torsion moment on the certain beam. Earthquake can cause dangerous torsion force in all elements of building constructions. Like the load outside the center of the mass in which the torsion stress can be very high. This research aims to find out the torsion capacity on hybrid high performance concrete beam element in which the hybrid high performance concrete using additive alternative materials, by using 7 test objects variations, the size of the test objects used is 20 x 25 x 120 cm3 and the test done for 28 days of concrete period. From the test output obtained  that the highest torsion moment found out in Test object number 6 (BU6) using pozzolanic fly Ash (10%) + fine aggregate of the sand pozzolan (10%) + coarse aggregate of  palm kernel shell (40%) + Nano material filler of iron ore as 10.4 kNm. The highest torsion angle is also created on BU6 as 0,0246 rad. The concrete performance highly affects the torsion strength, the highest concrete performance is found out from BU6 which is 59,48 MPa.